Acute gastrointestinal bleeding: proposed study outcomes for new randomised controlled trials. Issue 5 (20th July 2021) - Jensen, Dennis M.; Barkun, Alan; Cave, David; Gralnek, Ian M.; Jutabha, Rome; Laine, Loren; Lau, James Y. W.; Saltzman, John R.; Soetikno, Roy; Sung, Joseph J. Y.
Summary: Background: Acute gastrointestinal bleeding (GIB) remains a common cause of hospitalisation. However, interpretation and comparisons of published studies in GIB have been hampered by disparate study methodology. Aims: To make recommendations about outcome measures to be used in future randomised controlled trials (RCTs) of patients with acute bleeding from any GI source (nonvariceal UGI, variceal, small bowel, or colon) and suggest new RCTs in acute GIB for future peer‐reviewed funding. Methods: As part of a National Institutes of Health conference entitled "Hemostatic Outcomes in Clinical Trials", a group of GIB experts performed targeted critical reviews of available evidence with the goal of proposing a bleeding outcome that could potentially be applied to different disciplines. In addition, the panel sought to develop a clinically meaningful primary endpoint specifically for acute GIB, potentially allowing a more contemporary regrouping of clinically relevant outcomes. Results: The primary endpoint proposed was a composite outcome of further bleeding within 30 days after randomisation leading to red blood cell transfusion, urgent intervention (repeat endoscopy; interventional radiology or surgery), or death. Secondary outcomes may include the individual components of the primary outcome, length of hospitalisation, serious adverse events, and health care resource utilisation. Conclusion: The proposed endpoint may help move the GIB field forward by focusing on the most clinically relevant outcomes for patients with acute GIB of all types and informing study design and importance of sample size determination for future RCTs in GIB. Abstract : What is a new clinically relevant primary outcome measure for new randomized controlled trials (RCT's) of acute, severe gastrointestinal haemorrhage and what new RCT's are recommended for potential funding? An NIH Workshop of international experts recommended a composite outcome measure for new RCT's of all types of acute, severe GI haemorrhage, including non‐variceal and variceal upper GI, small intestinal, and colon bleeding. The primary endpoint is a composite outcome of further bleeding within 30 days after randomization leading to red blood cell transfusion, urgent intervention (repeat endoscopy; interventional radiology or surgery) or death directly or indirectly related to further bleeding. Secondary outcomes may include the individual components or the primary endpoint, length of hospitalization, serious adverse events, and health care resource utilization. Six new RCT's were described which may help governmental agencies decide which questions to focus on for supporting large, clinically important studies of acute GI haemorrhage.